Evaluasi Efikasi Antelmintik Albendazol Sebagai Obat Masal di Sekolah Dasar di Klungkung, Bali, Indonesia - Putu Indah Budi Apsari (WMJ (Warmadewa Medical Journal), 2021)
Abstract Soil transmitted helminthiasis still remains problem among tropic and subtropics developing countries worldwide. Contribute to more than a billion morbidities of people from children to adults. Children are the most affected population by this infection. This study aims to evaluate mass drug anthelminthic therapy of albendazole in school and preschool children. A cross sectional study recruited preschool and school-age children as subject of this research. During the period of May-July 2020, fecal samples were collected one month after albendazole treatment and examined by Kato kats technique. Total 130 samples were examined, and it was found that only 1 (0.007%) was positive for Trichuris trichiura. Accordingly, we can conclude that Albendazole is effective for treating Soil transmitted helminthiasis in preschool and school-age children. Keyword: anthelminthic, albendazole, school, children